Glagoli z oslabljenim pomenom v Slovarju slovenskega knjižnega jezika - Godec Soršak, Lara (Slavistična revija, 2013)
Based on previous findings and on the analysis of sample material, the author devised a typology of light verbs and criteria for defining the use of light verbs in Slovene.
Keywords: dictionary; glagol; grammar; jezikoslovje; language sciences; linguistics; slovar; Slovar slovenskega knjižnega jezika; Slovene; slovenščina; slovnica; verb